URGENSI KESIAPAN GURU DAN SEKOLAH TERHADAP PENERAPAN KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Ayyesha Dara Fayola; Ratih Rahmawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The Merdeka Program, as an alternative program to overcome the decline in the quality of learning during the pandemic, provides "learning freedom" to those responsible for implementing learning, especially teachers and school principals, in designing, implementing and developing. program. This research was conducted to provide an overview. The aim of the research is to reveal the importance of teacher and school readiness in implementing the Independent Learning Curriculum. The method used in this research is literature study. The results of the research conclude that there is a need for support and mentoring to strengthen the readiness of teachers in elementary schools in implementing the Independent Curriculum. This includes improving the quality of teacher human resources which are still inadequate, as well as improving learning facilities and resources that are limited or inadequate. The readiness of teachers, who have a central role in education, is very important in managing. Schools that want to be successful in implementing independent programs need to carry out effective learning activities in order to achieve the desired expectations.